Effectiveness of Health Education on Iron Supplement Adherence Among Adolescent Girls: A Scoping Review - Hariyani Sulistyoningsih; Ayun Sriatmi; Apoina Kartini; Syamsulhuda Budi Musthofa (Jurnal Kesehatan Komunitas Indonesia, 2026)
Anemia in adolescent girls affects cognitive performance, physical and mental health, social development, and increases the risk of anemia during pregnancy. Health education programs have been implemented to improve adherence with iron supplementation, yet evidence comparing the effectiveness of different approaches remains limited. This study aimed to map and synthesize evidence on the effectiveness of health education interventions in improving adherence to iron supplementation among adolescent girls. A scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) and the Joanna Briggs Institute (JBI) scoping review framework with PCC criteria: adolescent girls (Population); health education (Concept); adherence with iron supplementation (Context). Articles with no date restriction were retrieved from Scopus, PubMed, and EBSCO using predefined keywords. Data extraction included country, design, findings, and study limitations. Seven articles were included following title, abstract, and full-text screening. Thematic analysis was applied, and results were presented in tables and narrative form. Studies were conducted in India (n=4) and Indonesia (n=3), published between 2008 and 2025, involving samples ranging from 70 to 150,700 adolescent girls. All included studies reported a positive association between health education and improved adherence to iron supplementation, with adherence rates ranging from 26.5% in WhatsApp-based reminder interventions to 97.1% in teacher-supervised, directly observed treatment. Health education combined with direct supervision, family support, and digital reminders can effectively improve adolescent girls' adherence to iron supplementation. Subsequent studies should use standardized adherence indicators and longer follow-up periods to enhance comparability and generalizability.